Working memory program for improving language skills in older adults with mild neurocognitive disorders: A pilot study - Sutthiphan, Patcharanun; Rattakorn, Phuanjai; Chinchai, Supaporn; Wongpakaran, Nahathai; Tanprawate, Surat; Sirimaharaj, Nopdanai (Journal of Associated Medical Sciences, 2023)
Background: Older adults with mild neurocognitive disorders (mild NCD) have a higher risk of major NCD. Cognitive deterioration can cause a deficit in working memory and language. Recent studies have shown some involvement overlapping the brain structure of working memory and language skills. Therefore, working memory intervention effectively enhances language skills in mild NCD. However, more research on this topic in Thailand is required. Objectives: This study aimed to develop and implement a pilot study on a working memory program for improving language skills in older adults with mild NCD. Materials and methods: This study was a developmental research design with two phases. Phase one involved the development and examination of the content validity of the working memory program for improving language skills by five experts. Phase two involved piloting the program with three older adults with mild NCD. The participants were asked to provide suggestions about the clarity of content and images, language usage, font size, the comprehensibility of instructions in each activity, and the quality of audio files used to complement the program activities through semi-structured interviews. Descriptive statistics were employed to analyze the collected data. Results: The program comprised nine activities associated with the phonological loop, visual-spatial sketchpad, episodic buffer, and central executive tasks. The program’s content validity was evaluated by five experts, resulting in a content validity index of 0.94, meeting the established criteria. Among the pilot users, three participants meeting the specified criteria indicated their ability to use and practice the program at home effectively. While most participants agreed that the images were clear and the font size was appropriate, there were concerns regarding the clarity of the training process steps and instructions. Additionally, some participants encountered challenges in accessing audio files through quick response (QR) codes. Conclusion: In summary, the pilot study of the working memory program for improving language skills in older adults with mild NCD passed the content validity test and underwent revisions based on suggestions from the pilot users. Consequently, the program could enhance the language abilities of older adults with mild NCD. The next phase will investigate its effectiveness in improving language skills in older adults with mild NCD.